Development of E-module toward Mangrove Species Diversity Based on Local Potential of Pulau Dua Nature Reserve Serang Banten to Improve Students' Digital Literacy - Rachmawati, Rizqi Nur; Rohman, Fatchur; Novianti, Vivi (BIOEDUKASI, 2024)
This research is the development of e-modules of mangrove species diversity based on the local potential of Pulau Dua Nature Reserve Serang Banten which is a learning media to assist students in introducing the biodiversity of mangrove local potential around and used as teaching materials that are used independently. The purpose of developing this e-module is to produce teaching materials that are valid, practical and effective for use in learning. This local potential-based mangrove species diversity e-module development model uses the Lee & Owens (2004) development model. To see the validity of e-modules, validation of material experts, media experts and teaching materials and field practitioners was carried out. Practicality test with one to one trial of 3 students, small group trial of 12 students and field trial of 36 students. The effectiveness of e-modules was measured objectively using the Simple Paired T test and subjectively using the N-Gain Score on students' digital literacy. The results showed that the e-module of mangrove species diversity developed was valid, practical and effective. There are differences in students' digital literacy before and after being taught with e-modules of mangrove species diversity.